2016
DOI: 10.1017/s1751731115002748
|View full text |Cite
|
Sign up to set email alerts
|

Verification of suitable and reliable reference genes for quantitative real-time PCR during adipogenic differentiation in porcine intramuscular stromal-vascular cells

Abstract: Intramuscular fat (IMF) is an important trait influencing meat quality, and intramuscular stromal-vascular cell (MSVC) differentiation is a key factor affecting IMF deposition. Quantitative real-time PCR (qPCR) is often used to screen the differentially expressed genes during differentiation of MSVCs, where proper reference genes are essential. In this study, we assessed 31 of previously reported reference genes for their expression suitability in porcine MSVCs derived form longissimus dorsi with qPCR. The exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…The most frequently used housekeeping genes, GAPDH , B-actin , and 18S [ 9 ], were not identified as ideal endogenous control genes in this study, agreeing with the findings of Nygard et al (2007) [ 34 ], Cinar et al (2012) [ 35 ], Zhang et al (2012) [ 20 ], Gessner et al (2013) [ 36 ], Li et al (2016) [ 37 ], and Wang et al (2016) [ 7 ], but contradicting the findings of Erkens et al (2006) [ 14 ], Kuijk et al (2007) [ 26 ], and Li et al (2011) [ 38 ]. Because RT-qPCR has dynamic range and increased sensitivity compared with traditional quantitation techniques, the well-known housekeeping genes, especially GAPDH , B-actin , and 18S , have been shown to be significantly affected by biological processes, different experimental treatments, and different cell types and tissues [ 39 ].…”
Section: Discussionsupporting
confidence: 89%
“…The most frequently used housekeeping genes, GAPDH , B-actin , and 18S [ 9 ], were not identified as ideal endogenous control genes in this study, agreeing with the findings of Nygard et al (2007) [ 34 ], Cinar et al (2012) [ 35 ], Zhang et al (2012) [ 20 ], Gessner et al (2013) [ 36 ], Li et al (2016) [ 37 ], and Wang et al (2016) [ 7 ], but contradicting the findings of Erkens et al (2006) [ 14 ], Kuijk et al (2007) [ 26 ], and Li et al (2011) [ 38 ]. Because RT-qPCR has dynamic range and increased sensitivity compared with traditional quantitation techniques, the well-known housekeeping genes, especially GAPDH , B-actin , and 18S , have been shown to be significantly affected by biological processes, different experimental treatments, and different cell types and tissues [ 39 ].…”
Section: Discussionsupporting
confidence: 89%
“…One microgram RNA was reverse-transcribed with standard reagents (Biocolors, China). The primers for SCFA uptake [monocarboxylate transporter 1 ( MCT1 )] ( Haenen et al, 2013 ), pro-inflammatory cytokines ( IL-6, IL-8, IL-1β, IL-12p40, IL-18, TNF-α , and IFN-γ ) ( Pié et al, 2004 ; Feng et al, 2014 ; Tudela et al, 2015 ), anti-inflammatory cytokine ( IL-10 and TGF-β ) ( Pieper et al, 2012 ; Feng et al, 2014 ), gene expression regulator [histone deacetylase 1 ( HDAC1 )] ( Lee et al, 2011 ), tight junction protein genes [zonula occludens-1 ( ZO-1 ) and occludin] ( Feng et al, 2014 ), intestine development-related genes [insulin-like growth factor-1 ( IGF-1 ), preproglucagon, IGF-1R , and epidermal growth factor ( EGF ) ( Xiang, 2011 ; Han et al, 2012 ) and housekeeping genes (β-actin and GAPDH ) ( Li et al, 2016 ; Zhang et al, 2017 ) used in this study are presented in Supplementary Table 2 . The target genes and housekeeping genes were measured by quantitative real-time PCR with SYBR Green (Roche, Switzerland) and fluorescence was detected on an ABI 7300 sequence detector.…”
Section: Methodsmentioning
confidence: 99%
“…Intramuscular fat (IMF), corresponding to pork marbling, refers to the fat located within muscles, which is associated with the number and size of intramuscular adipocytes [ 1 ]. Previous studies have indicated that IMF is closely related to flavor, juiciness, and tenderness [ 2 , 3 ]; lower IMF content results in dry and less-flavorful meat, and IMF content is positively associated with sensory quality traits of meat and consumer acceptability [ 4 ]. When IMF content increases from 1 to 3%, sensory quality is significantly improved [ 5 ].…”
Section: Introductionmentioning
confidence: 99%